Characterization of the Stereochemical Structures of 2H‐Thiazolo[3, 2‐a]pyrimidine Compounds and Their Binding Affinities for Anti‐apoptotic Bcl‐2 Family Proteins. Issue 8 (21st June 2013) - Xu, Yaochun; Zhou, Mi; Li, Yan; Li, Chengke; Zhang, Zhengxi; Yu, Biao; Wang, Renxiao
Abstract In a previous study we reported a class of compounds with a 2H‐thiazolo[3, 2‐a]pyrimidine core structure as general inhibitors of anti‐apoptotic Bcl‐2 family proteins. However, the absolute stereochemical configuration of one carbon atom on the core structure remained unsolved, and its potential impact on the binding affinities of compounds in this class was unknown. In this study, we obtained pure R and S enantiomers of four selected compounds by HPLC separation and chiral synthesis. The absolute configurations of these enantiomers were determined by comparing their circular dichroism spectra to that of an appropriate reference compound. In addition, a crystal structure of one selected compound revealed the exocyclic double bond in these compounds to be in the Z configuration. The binding affinities of all four pairs of enantiomers to Bcl‐xL, Bcl‐2, and Mcl‐1 proteins were measured in a fluorescence‐polarization‐based binding assay, yielding inhibition constants (Ki values) ranging from 0.24 to 2.20 μM. Interestingly, our results indicate that most R and S enantiomers exhibit similar binding affinities for the three tested proteins. A binding mode for this compound class was derived by molecular docking and molecular dynamics simulations to provide a reasonable interpretation of this observation.